Impact and Possible Mechanism(s) of Adipose Tissue-Derived Mesenchymal Stem Cells on T-Cell Proliferation in Patients With Rheumatic Disease - Kuca-Warnawin, Ewa; Olesińska, Marzena; Szczȩsny, Piotr; Kontny, Ewa (Frontiers in Physiology, 2022)
Objectives: Systemic lupus erythematosus (SLE) and systemic sclerosis (SSc) are chronic wasting, incurable rheumatic diseases of autoimmune background, in which T-cells play critical pathogenic role. Autologous ASCs may represent alternative therapeutic option for SLE and SSc patients, but biology of these cells is poorly understood. Methods: Herein, we evaluated the anti-proliferative impact of ASCs of healthy donors (HD/ASCs, 5 reference cell lines), SLE (n=20) and SSc (n=20) patients, on T lymphocytes. To asses indirect and direct pathway of ASCs action, peripheral blood mononuclear cells (PBMCs) and purified CD4+ T-cellsof HD were activated and co-cultured in cell-to-cell contact (C-C) and transwell (T-W) conditions with untreated or cytokine (TNF+IFNΥ, TI)-licensed ASCs, then analysed by flow cytometry to rate proliferation response of CD8+ and/or CD4+ T-cells. The concentrations of of kynurenines, prostaglandin E2 (PGE2), interleukin 10 (IL-10), and transforming growth factor β (TGFβ) were measured in culture supernatants. Specific inhibitors of these factors (1-MT, indomethacin, and cytokine neutralizing antibody, respectively) were used to assess their contribution to anti-proliferative ASCs action. Results: All tested ASCs significantly decreased the number of proliferating CD4+ and CD8+ T-cells, the number of division/proliferating cell (PI), and fold expansion (RI), and similarly up-regulated kynurenines and PGE2, but not cytokine levels, in the co-cultures with both types of target cells. However, TI-treated SLE/ASCs and SSc/ASCs exerted slightly weaker inhibitory effect on CD4+ T-cell replication than respective HD/ASCs. All ASCs acted mainly via soluble factors. Their anti-proliferative effect was stronger and kynurenine levels were higher in T-W than C-C conditions. Blocking experiments indicated an involvement of kynurenine pathway in inhibiting both the number of proliferating cells, PI, and RI values as well as PGE2 PGE2 role in decreasing the number of proliferating cells. TGFβdid not contribute to ASCs anti-proliferative capabilities while IL-10 seems to be involved in such activity of only SLE/ASCs. Conclusions: The results indicate that SLE/ASCs and SSc/ASCs retain their capability to restrain expansion of allogeneic CD4+ and CD8+ T-cells, act by similar mechanisms as ASCs of healthy donors, and thus may have therapeutic value.